Phytochemical Analysis of Cynometra Madagascariensis (Fabaceae), a Malagasy Medicinal Plant - Andrianarijaona Mamy; Ralaivaon-Dratsitonta Jumaël Edith Fabrice; Fatiany Pierre Ruphin; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2025)
A comprehensive phytochemical and physicochemical investigation was conducted on the bark of Cynometra madagascariensis, a plant of the Fabaceae family traditionally used in Madagascar to treat and heal wounds and burns. Sequential maceration extractions were performed with solvents of increasing polarity (hexane, dichloromethane, and methanol) to obtain a range of crude extracts. Subsequent phytochemical screening revealed a diverse chemical profile, with a significant presence of tannins and terpenoids, and lower concentrations of quinones and saponins. Alkaloids, coumarins, flavonoids, and steroids were notably absent from the bark. Chromatographic methods were then employed for the separation and isolation of constituents from the hexane extract. Thin-layer chromatography (TLC) was utilized to optimize the mobile phase and monitor the fractionation process. This led to the successful isolation of a pure compound, designated F58-60, through column chromatography. The structure of this molecule was elucidated using one-dimensional NMR spectroscopy (1H and 13C NMR). A comparative analysis of the spectroscopic data with published literature confirmed the compound's identity as di(2-ethylhexyl) phthalate. This research provides a foundational understanding of the chemical composition of this medicinal plant and paves the way for further studies on the biological activities of its constituents.